Examining hospice enrollment through a novel lens: Decision time. Issue 2 (13th July 2016) - Wallace, Cara L.
Abstract: Objective: No prior studies on hospice utilization have captured information about the amount of time between when one first learns of hospice as a potential option for care and when he/she actually enrolls. Little is in fact known about this decision-making process. The present study examines hospice enrollment by exploring relationships between hospice decision time and known barriers to care. Method: This was an exploratory cross-sectional study. Pearson's r was employed to identify bivariate relationships between barriers to care and decision time for hospice care. Independent-sample t tests and ANOVA were utilized to consider differences in decision time across key variables. Results: Some 90 hospice patients, or their primary decision maker, participated in the study from a not-for-profit hospice located in the southern United States. Decision time was correlated with referral source, use of disease-directed treatment, functional status (on the Palliative Performance Scale [PPS]), age, diagnosis, income, race, and spirituality—suggesting that decision time is a pertinent variable when examining hospice utilization. Differences in decision time were found across diagnosis, race, income, and referral source. Significance of results: This study provides implications for policy and practice, particularly for clinicians faced with initial conversations about hospice care. Differences in decision time highlight ongoing needs related to overcoming healthcare disparities, the important role of including families in initial conversations, and the potential need for varied approaches to talking about hospice care based upon diagnosis. Results also highlight the need for policies supportive of concurrent care, where hospice can be accessed alongside curative care.